Menjadi Dosen Profesional dan Inspiratif - Supriyadi Ahmad (SALAM: Jurnal Sosial dan Budaya Syar-i, 2016)
Abstract:Professional and inspirational lecturer become the dream of every academician. Professional lecturer is professional teacher and scientist with the primary task of transforming, developing, and disseminating science, technology, and the arts through education, research, and social community. Professional lecturer must have pedagogic, professional, good personality, and social competence. In order to be inspirative, lecturer must have the sense of never ending learning, competence, sincere, spiritual, total, motivator, creative, inovative, and discipline.Keyword: Lecturer, Professional, Inspirative. Abstrak: Dosen profesional dan inspiratif menjadi dambaan setiap insan akademik. Dosen profesional adalah pendidik profesional dan ilmuwan dengan tugas utama mentransformasikan, mengembangkan, dan menyebarluaskan ilmu pengetahuan, teknologi, dan seni melalui pendidikan, penelitian, dan pengabdian kepada masyarakat. Dosen profesional harus mempunyai kompetensi pedagogik, profesional, kepribadian, dan sosial. Agar menjadi inspiratif, dosen harus mempunyai sifat haus ilmu sehingga terus-menerus belajar, terus belajar, kompeten, ikhlas, spiritualis, totalitas, motivator dan kreatif, pendorong perubahan, dan disiplin.Kata Kunci: Dosen, Profesional, Inspiratif.